Pengaruh Green Accounting dan Sustainability Report Terhadap Return on Assets dengan Mediasi Investasi Lingkungan - Kasih, Annisa Tiara; Priyastiwi, Priyastiwi (Juara: Jurnal Riset Akuntansi, 2025)
Environmental sustainability represents a critical dimension in both business operations and societal wellbeing. Raw material companies, whose operations inherently depend on natural resources, are expected to maintain environmental standards in accordance with regulatory frameworks. This study investigates the relationship between sustainability reports and green accounting practices on return on assets, with environmental investment serving as a mediating variable. The research employs quantitative methodologies, focusing on raw goods sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The analytical framework utilizes multiple linear regression, with sample selection conducted through purposive sampling, yielding 31 companies and 93 combined annual and sustainability reports that met the established criteria. The findings reveal that green accounting shows a significant positive effect on return on assets, while sustainability report has no significant effect on return on assets. Furthermore, environmental investment effectively mediates the relationship between green accounting and return on assets but fails to mediate the connection between sustainability reporting and return on assets. These results suggest that companies aligning their operational capabilities with environmental considerations can indirectly enhance their return on assets performance.